Peran Relasi Orang Tua-Anak dan Tekanan Teman Sebaya terhadap Kecenderungan Perilaku Pengambilan Risiko - Friska Tri Andayani; Endang Ekowarni (Gadjah Mada Journal of Psychology (GamaJoP), 2016)
Alsa, A. (2014). Pendekatan kualitatif dan kuantitatif serta kombinasinya dalam penelitian psikologi. Cetakan V. Yogyakarta: Pustaka Pelajar.Badan Koordinasi Keluraga Berencana Nasional (BKKBN). (2011). Kajian profil penduduk remaja (10-24 tahun): Ada apa dengan remaja. Policy Brief Puslitbang Kependudukan. Retrieved fromhttp://www.depkes.go.id/resources/download/pusdatin/infodatin/infodatin%20reproduksi%20remaja-ed.pdfBadan Pusat Statistik (BPS). (2012). Survei demografi dan kesehatan Indonesia 2012. Kesehatan Reproduksi remaja. Jakarta: Kementerian Kesehatan Jakarta. Retrieved from http://www.bkkbn.go.id/litbang/pusdu/Hasil%20Penelitian/SDKI%202012/Laporan%20Pendahuluan%20REMAJA%20SDKI%202012.pdfBadan Pusat Statistik Provinsi D.I. Yogyakarta. (2015). Statistik politik dan keamanan Provinsi Daerah Istimewa Yogyakarta. Yogyakarta: Badan Pusat Statistik.Baumrind, D., Larzele, R. E., & Owens, E. B. (2010). Effect of preschool parents’ power assertive patterns ang practise on adolescent development. Parenting Science and Practice, 10(3), 157-201.Bonino, Cattelino, & Clairano,. (2005). Adolescents and risk, behavior, functions, and protective factors. Italia: Springer.Burt, S.A., McGue, M., Lacono, W.G., & Krueger, R.F. (2006). Differential parent–childrelationships and adolescent externalizing symptoms: Cross-lagged analyses within a monozygotic twin differences design. Devevelopmental Psychology, 42, 1289–1298.Chein, J., Albert, D., O’Brien, L., Uckert, K., & Steiberg, L. (2011). Peer increase adolescent risk taking by enhancing activity in the brain’s reward circuitry. Journal Development Science, 14(2), F1-F10.Choo, H., & Shek, D. (2013). Quality of parent-child relationship, family conflic, peer pressure, and drinking behaviours of adolescents in an Asian context: the case of Singapore. Social Indication Rescue, 110, 1141-1157.Clasen, D. R., & Brown, B. B. (1987). Understanding peer pressure in the middle school. Journal of Adolescence, 19(1), 21-23.Crawford, L. A., & Novak, K. B. (2002). Parental and peer influences on adolescent drinking: The relative impact of attachment and opportunity. Journal of Child & Adolescent Substance Abuse, 12(1), 1-26.Crockett, L. J., Raffaelli, M., & Shen, Y. L. (2006). Linking self-regulation and risk proneness to risky sexual behavior: Pathways through peer pressure and early substance use. Journal of Research on Adolescence, 16(4), 503-525.Derek, K., & Smiler, A. P. (2013). Norms and peer pressure in adolescent boys and girls alcohol use, Substance Use Misuse, 48(5), 371-378.DiClemente, R. J., Santelli, J. S., & Crosby, R. A. (2009). Adolescent health. Understanding and preventing risk behaviour. San Franscisco: Jossey-Bass: A Wiley Imprint.Dixson, M., Bermes, E., & Fair, S. (2014). An Instrument to investigate expectations about and experiences of the parent-child relationship: The parent-child relationship schema scale. Social Science, 3, 84-114.Eaton, D. K., Kann, L. & Kinchen, S. (2006). Youth risk behavior surveillance. Division of Adolescent and School Health, National Center for Chronic Disease Prevention and Health Promotion,55(5),1-108.Faska. (2015, April 5). Pernikahan dini di Jogja meningkat tajam. Pojoksatu. Retrieved fromhttp://pojoksatu.id/news/berita-nasional/2015/04/05/pernikahan-dini-di-jogja-meningkat-tajam/Fisher, L., & Feldman, S. S. (1998). Familial antecedents of young adulth health risk behavior: A longitudinal study. Journal of Family, 12(1), 68-80.Gardner, M. & Steinberg, L. (2005). Peer influence on risk taking, risk preference, and risky decision making in adolescence and adulthood: An experimental study. Developmental Psychology, 41(4), 625–635.Garnefski, N., & Diekstra, R. F. W. (1996). Perceived social support from family, school, and peers: Relationship with emotional and behavioral problem among adolescents. Journal of the American Academy of Child and Adolescent Psychiatry, 35(12), 1657-1664.Gheorghiu, A., Delhomme, P., & Felonneau, M. L. (2015). Peer pressure and risk taking in young drivers’ speeding behavior. Transportation Research Part F, 35, 101–111.Ghozali, I. (2011). Aplikasi analisis multivariat dengan program IBM SPSS 19, Edisi kelima. Semarang: Universitas Diponegoro.Gullone, E. & Moore, S. (2000). Developing adolescents: A reference for professionals. Washington DC: American Psychological Association.Informasi Kementerian Pemuda dan Olahraga. (2009). Kementerian pemuda dan olahraga. Biro Perencanaan: Sekretariat Kementerian Pemuda dan Olahraga.Jahun, K. (2011). Patterns of parent-child relationship quality, parent depression and adolescent development outcomes (Disertasi tidak terpublikasi). University of Washington, School of Nursing. Jessor, R., & Jessor, T. (2009). Description versus explanation in cross-national research on adolescent. Journal of Adolescent Health, 43(6), 527-528.Jessor, R., Turbin, M.S., Costa, F.M., Dong, Q., Zhang, H., & Wang, C. (2003). Adolescent problem behavior in China and the United States: A cross-national study of psychosocial protective factors. Journal of Adolescence Research,13, 329–360.Johnson, & Matthew, D. (2013). Parent-child relationship quality directly and indirectly influences hooking up behaviour reported in young adulthood through alcohol us in adolescence. Arch Sex Behaviour, 42, 1463-1472.Karriker-Jaffe, K. J., Foshee, V. A., Ennett, S. T., & Suchindran, C., (2008). The development of aggression during adolescence: Sex differences intrajectories of physical and social aggression among youth in rural areas. Journal Abnormal.Child Psycholology, 36, 1227–1236.Kementerian Dalam Negeri (Kemendagri). (2014). Kode dan data wilayah administrasi pemerintahan. Jakarta: Ditjen Kependudukan dan Catatan Sipil Kemendagri Per Semester I.Klahr, A.M., McGue, M., Lacono, W.G., & Burt, S.A. (2011). The association between parent–child conflict and adolescent conduct problems over time: Results from a longitudinal adoption study. Journal Abnormal Psychology, 120, 46–56.Masten, A. S. (2001) Resiliensi process in development. American Psichological Association, 56(3), 227-228.Mathijssen, J. P. J., Janssen, M. M., Bon-Martens, M., Oers, H. A., Boer, A. D., & Garretsen, H. F. (2014). Alcohol segment-specific associations between the quality of the parent-child relationship and adolescent alcohol use. Journal of Public Health, 872, 1471-2458.Leather, N. C. (2009). Risk-taking behaviour in adolescence: A literature review. Journal of Child Health Care,13(3), 295–304. Oni, A. A. (2010). Peer group pressure as a determinant of adolescent social adjustment in Nigerian schools. Asian Pasific Journal of Educators and Education, 25, 189-202.Peacock, A., & Bruno, R. (2015). Young adults who mix alcohol with energy drink: Typology of risk taking behaviour. Addictive Behaviours, 45, 252-258.Qu, Y., Fuligni, A. J., Galvan, A., & Telzer, E. H. (2015). Buffering effect of positive parent–child relationships on adolescent risk taking: A longitudinal neuro imaging investigation. Developmental Cognitive Neuroscience, 15, 26–34.Ritcher. (2010). Risk behavior in adolescence, patterns, determinants, and consequences. Germany: Springer Fachmedien.Sales, J. M., & Irwin, C. E., Jr. (2009). Theories of adolescent risk-taking: A biopsychosocial model. In R. DiClemente & R. Crosby (Eds.), Adolescent health:Understanding and preventing risk behaviors andadverse health outcomes (pp. 31–50). San Francisco, CA: Jossey-Bass.Santrock, J. W. (2003). Adolescene: Perkembangan remaja. Jakarta: Erlangga.Savitri, A. R. (2015, Desember 11). Inilah organisasi paling nge-hits di Yogyakarta. Youth Forum. Retrieved from http://www.duniaremaja. jogjaprov.go.id/detilberita/14/1/Inilah-Organisasi-Paling-Nge-Hits-di-Yogyakarta,-YouthForum-DIYSkaar, N. R. (2009). Development of the adolescent exploratory and health risk behaviour rating scale(Unpublished dissertation). University of Minnesota, United Stated.Sofronoff, Dalgliesh, & Kosky. (2004). Out of options, a cognitive model of adolescent suicide and risk-taking. USA: Cambridge University Press.Stattin, H., & Kerr, M. (2000). Parental monitoring: A reinterpretation. Child Developmental, 71, 1072-1085.Survei Demografi dan Kesehatan Indonesia. (2013). Kesehatan reproduksi remaja. Badan Pusat Statistik. Jakarta: Indonesia.Tsai, K. M. (2013). Continuity and discontinuity in perceptions of family relationship from adolescence to young adulthood. Journal of Child Development, 84(2), 471-484.Turley, R. N. L., Desmond, M., & Bruch, S. K. (2010). Unanticipated educational consequences of a positive parent-child relationship. Journal of Marriage and Family, 72(5), 1377-1390.